COMPARISON OF HYBRID MAIZE PRICE FEASIBILITY BY MARKETING CHANNEL - Rakassiwi Nenti; Reny Sukmawani; Neneng Kartika Rini (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
Price viability is essential for improving farmers’ welfare. This study aims to analyze the feasibility of the prices received by hybrid maize farmers in the Jampang Tengah Subdistrict of Sukabumi District. The method employed is descriptive quantitative analysis, utilizing the Farmer’s share value indicator, which represents the percentage of the price received by farmers compared to the consumer selling price. The results indicated that in channel I (farmer-consumer), the price received was IDR 5,300, resulting in a Farmer’s share of 100%. In channel II (farmer-major trader-consumer), the price received by farmers was IDR 4,500, resulting in a Farmer’s share of 85.71%. In channel III (farmer-collecting trader-large trader-consumer), the price received by farmers was IDR 4,000, leading to a Farmer’s share of 76.92%. Based on these results, the price received by farmers was deemed feasible because the Farmer’s share value exceeded 40% across all distribution channels.